Occupational Diseases, Causes and Preventive Measures (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article describes the modern general theoretical aspects of occupational pathology, and also covers the general principles of classification, treatment and prevention of occupational diseases.